Answer:
12
Step-by-step explanation:
h(x) = f(g(x))
Using chain rule:
h'(x) = f'(g(x)) g'(x)
h'(1) = f'(g(1)) g'(1)
h'(1) = f'(2) g'(1)
h'(1) = -4 × -3
h'(1) = 12
Answer: 5
Because the two angles are congruent, these sides are congruent, so:
5x-8=2x+7
3x=15
x=5
4.2³ = 74.088. If the 4.2 is accurate, this is actually not an estimate but an exact answer. You can of course round it to 74, then it becomes an estimate.
Answer:
5
Step-by-step explanation:
y^1 = 5^1 (y = 5)
Anything raised to the power of 1 is just itself.
So, 5^1 = 5